Gas-liquid flow generated by a Rushton turbine in stirred vessel: CARPT/CT measurements and CFD simulations - Khopkar, A. R.; Rammohan, A. R.; Ranade, V. V.; Dudukovic, M. P. (Chemical Engineering Science, 2005)
In this work, computer-automated radioactive particle tracking (CARPT), computed tomography (CT) and computational fluid dynamic (CFD) based models were used to investigate gas-liquid flow generated by a Rushton turbine. CARPT and CT measurements were carried out in a gas-liquid stirred vessel operating in two different flow regimes and captured the quantitative Eulerian information of gas-liquid flow. The CARPT data was then used to extract the circulation tune distribution in a vessel. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence (along the lines proposed by Brucato et al. (Chem. Eng. Sci. 45(1998) 3295)) were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). Most model predictions compared favourably with CARPT and CT measurements. Validated CFD models as attempted in this paper are promising to simulation of industrial stirred vessels. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CARPT; CFD; CT; gas-liquid flow; stirred vessel

CFD simulation of gas-liquid stirred vessel: VC, S33, and L33 flow regimes - Khopkar, A. R.; Ranade, V. V. (AICHE Journal, 2006)
A comprehensive computational model based on the Eulerian-Eulerian approach was developed to simulate gas-liquid flows in a stirred vessel. A separate submodel was developed to quantitatively understand the influence of turbulence and presence of neighboring bubbles on drag acting on bubbles. This submodel was used to identify an appropriate correlation for estimating the interphase drag force. The standard k-epsilon turbulence model was used to simulate turbulent gas-liquid flows in a stirred vessel. A computational snapshot approach was used to simulate motion of the standard Rushton turbine in a fully baffled vessel. The computational model was mapped onto FLUENT4.5, a commercial CFD solver. The model predictions were compared with the previously published experimental data of Bombac and co-workers. The model was used to simulate three distinct flow regimes in gas-liquid stirred vessels: vortex clinging (VC), alternating small cavities (S33), and alternating large cavities (L33). The predicted results show reasonably good agreement with the experimental data for all three regimes. The computational model and results discussed in this work would be useful for understanding and simulating gas holdup distribution and flow regimes in stirred vessels. (c) 2006 American Institute of Chemical Engineers.
Keywords: computational fluid dynamics (CFD); Flow regimes; gas holdup distribution; Rushton turbine; stirred vessel

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

Effect of different operational conditions on the decolorization of molasses spent wash using once developed soil inoculum - Adikane, H. V.; Dixit, J. N. (Biodegradation, 2009)
A stirred vessel coupled with membrane unit containing cellulose acetate (0.45 mu m) membrane was used to study the decolorization of anaerobically digested molasses spent wash (MSW). The soil collected from the MSW disposal site was used as inoculum to study the decolorization without addition of any additives. The same inoculum was used over a period of 163 days at room temperature to study the decolorization of 12.5-50% (v/v) MSW using different operational conditions. The reactor was entered in to the inhibition mode after the feeding of 50% MSW, which was restored 100% without changing any operational condition. The maximum decolorization obtained for 12.5% (v/v) MSW was 77.22 +/- A 0.13%. The decolorization achieved for 25, 37.5, and 50% (v/v) MSW was 70.41 +/- A 0.12, 56.47 +/- A 0.17, and 48.78 +/- A 0.09%, respectively. Increase in the utilization of protein and reducing sugar was observed up to 25% MSW whereas, higher concentration showed decrease in the utilization. Results indicate 63% removal of chemical oxygen demand for 12.5% (v/v) MSW. Membrane flux which was significantly reduced after the feeding of 50% MSW was regenerated without changing the washing procedure, however, 35% decrease in sample flux was observed over the continuous use of membrane for the period of 198 days.
Keywords: Decolorization; Membrane flux; Molasses spent wash; Soil as inoculum; stirred vessel

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel